Etologia canina, comportamento humano e educação ambiental no Centro de Controle de Zoonoses de Campina Grande/PB: um estudo sobre o bem-estar animal - Arruda, Katiana Barbosa de (2018)
In urban centers, it is estimated that there is one dog for every five inhabitants, and 10% of these animals are at risk on the streets, causing a series of damages to municipalities and the population, such as: urban disorder, the environment, visual pollution, overcrowding of kennels and, perhaps, the most worrying of all damages, the threat to collective health. It is that the lack of population control of dogs in urban centers, as well as the improper handling of these animals, has caused the proliferation of pathogenic organisms, such as zoonoses - transmissible diseases between humans and animals - that could endanger people's health . In addition, animals housed in surveillance and zoonoses are also at risk, since many of these entities do not have the physical structure, financial and human resources to meet the basic needs of the animal population, the environment and the well-being of species. Therefore, the main objective of this research was to analyze the situation of the dogs housed in the Zoonoses Control Center of Campina Grande / PB, based on the behavioral study of these animals, using as a parameter the five animal welfare requirements proposed by the Brambell. For this research, a case study, the focal animal observation method was used, without the interference of the researcher, with elaboration, application and etogram evaluation. It was verified that the behaviors exhibited by the dogs in the Zoonoses Control Center of Campina Grande are consistent with the environmental conditions in which they were and are submitted, as well as with the stimuli and handling received by the people in the Unit in which they are confined. The results demonstrated that in the confinement process, the dogs failed to present an important amount of behavioral states. In relation to the concept of the five freedoms, it was concluded that the frequency of behavioral states presented by dogs proved to be inadequate for the pattern of the species, compromising the well-being and freedom of the animals analyzed, especially with regard to nutritional, behavioral and psychological requirements, due to the limited knowledge of the animals' needs, the incorrect handling of the canine species and the structural inadequacies of the facilities.